La monnaie, la politique et la possibilité d’un mode de développement à nouveau fondé sur le marché intérieur au Brésil et en Argentine - Jaime Marques Pereira (Revue de la Régulation)
The question asked in this paper is whether the acceleration of growth through a redistributive demand policy in Argentina and Brazil during the last decade means an emerging development model that would give back to the internal market the main growth impulse function it had before liberalization. The analysis focuses on the government of collective action. The making of expectations is studied as object of a governing system of monetary income promises, tied to the persuasive power of the discourse on the development model. Based on a conception of money as a symbolic, political and economic fact, the expectations are analyzed as a cognitive operation located in history, structured by the three facets of money: (i) a symbolic form as a unit of account whose acceptance is based on a development model driving a long-term visibility; (ii) an institution demonstrating the political power that guarantees an issuance and exchange regime in which credibility stands medium-term predictability ; (iii) a market value of means of payment defining in the short-term the value of the various types of income received or to be received. This analysis shows that the opposed choices of a competitive or appreciated exchange rate in Argentina and Brazil, associated respectively to an accommodating or restrictive monetary regime, reflect the agency of historically specific interest groups, both implying a gridlock in the transition to a new development model because they are still equally submitted to the monetary power of the creditors in the trade-off between taxation and public debt, which impedes changing the financing structure of the economy as well as sufficient increases in the investment in the domestic sector.